1995
DOI: 10.1128/jvi.69.11.6994-7000.1995
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus infection: effect of time and target cell number

Abstract: Using a model amphotropic recombinant retrovirus encoding the Escherichia coli lacZ gene and quantitative assays to measure virus infection, we have determined the effects of time and target cell number on infectivity. Infection of various numbers of NIH 3T3 fibroblasts showed that the extent of lacZ virus infection was dependent on virus concentration and independent of target cell number. These results demonstrate that multiplicity of infection is not an accurate predictor of the efficiency of retroviral inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(40 citation statements)
references
References 47 publications
(57 reference statements)
1
38
0
1
Order By: Relevance
“…5B). Interestingly, previous studies showed that prolonging the incubation time for up to 24 h led to increased retrovirus transduction efficiency (Morgan et al, 1995), but those studies reported that virus adsorption ceased after 2 h. In this study, Q-PCR confirmed that the increase in incubation time linearly increased the number of viral genes entering the cells, suggesting that adsorption continued for at least 8 h. The discrepancy between the previous and present results may be due to the varying mechanisms of virus adsorption into different cells because various factors and receptors (e.g., electrostatic interactions, phospholipids) involved in virus binding and entry have been proposed (Duisit et al, 1999;Tani et al, 2001). Although the current protocol successfully increased transduction efficiency and overall transgene expression, it is noteworthy that this approach may require modification when being applied to different cells, because cells of various origins respond differently under different incubation conditions (surrounding solutions, incubation time and temperatures, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…5B). Interestingly, previous studies showed that prolonging the incubation time for up to 24 h led to increased retrovirus transduction efficiency (Morgan et al, 1995), but those studies reported that virus adsorption ceased after 2 h. In this study, Q-PCR confirmed that the increase in incubation time linearly increased the number of viral genes entering the cells, suggesting that adsorption continued for at least 8 h. The discrepancy between the previous and present results may be due to the varying mechanisms of virus adsorption into different cells because various factors and receptors (e.g., electrostatic interactions, phospholipids) involved in virus binding and entry have been proposed (Duisit et al, 1999;Tani et al, 2001). Although the current protocol successfully increased transduction efficiency and overall transgene expression, it is noteworthy that this approach may require modification when being applied to different cells, because cells of various origins respond differently under different incubation conditions (surrounding solutions, incubation time and temperatures, etc.).…”
Section: Discussionmentioning
confidence: 99%
“…Similar experiments were conducted in the absence of Polybrene, except the cells were incubated with virus for 4 h instead of 2 h. After incubation with the virus, the cells were washed two times with 100 µL/well of fresh medium. The posttreated cells were then incubated for 2 d at 37°C with 100 µL of fresh medium and brought to either 20 µg/mL CSB or 10 µg/mL CSPG until confluent, and then they were tested for -galactosidase activity with the transduction efficiency assay as previously described (18,19). All other cells (control, pretreated, and cotreated) were incubated for 2 d at 37°C with 100 µL of fresh medium until confluent and then tested for -galactosidase activity.…”
Section: Methodsmentioning
confidence: 99%
“…The amphotropic packaging cell line ψ -CRIP, producing the R-SGC-lacZ virus, was kindly provided by L. K. Cohen of Somatix Therapy Corp., Alameda, CA (17). LacZ virus-containing medium was harvested from confluent cultures of the virus-producing cell line (overnight incubation of 10 mL of culture medium in a 10-cm tissue culture dish), filter sterilized (0.45 µm), and then stored at -85°C for later use (18).…”
Section: Introductionmentioning
confidence: 99%
“…Also, in the absence of cell lysate, the number of transduced cells increased with target cell concentration, whereas the transduction efficiency remained constant except at the lowest concentration of target cells (1.0 Â 10 5 cells/mL). Decreased transduction efficiency at low target cell concentration has previously been reported but this phenomenon remains unexplained (Hanenberg et al, 1997;Morgan et al, 1995). To probe whether this was possibly an artifact of the low cell concentration or potentially delayed expression, the cells were expanded for an additional 2 days and transduction efficiency was measured a second time.…”
Section: Effect Of Target Cell Concentrationmentioning
confidence: 99%